Sharia banking dynamics and the macroeconomic responses: evidence from Indonesia - Mansur, Alfan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Sharia banking industry in Indonesia has been established since early 1990s and growing remarkably after 1998. How the industry contributed to the Indonesian economy and what shocks drove the sharia banks’ credit in Indonesia were investigated in this paper using a Structural Vector Auto-regression (SVAR) model with recursive short run restrictions as its identification strategy. The results showed that GDP growth, core inflation, and business activity responded to increase in sharia banks’ financing positively, but with lags. Expanding sharia financing by 1 per cent boosted up GDP growth by 0.06 per cent. In the short-run, the contribution of sharia banks’ financing to the macroeconomic variables was limited, but it then escalated in the long run with the main channel of transmission through its ability to drive people’s purchasing power. Another result showed that sharia banks’ financing had a negative relationship with the Government’s monetary policy. In order to improve the performance of sharia banking in Indonesia, the demands of domestic sharia financing have to be strengthened with regards to the large number of Moslems in Indonesia. At the same time, Islamic banks have to improve their business processes. Rather than capping their profit margins or murabahah-based financing, they should promote more profit sharing mudharabah-based financing with prioritizing principle of mutual help among Moslems.